Development of an Android based Game Interfaced with QR Codes for a Gamified Power Management System - Cayabyab, Mariano Jesus M (Archīum Ateneo, 2015)
Filipinos are under the threat of an energy shortage. While efforts are being done both in the public and private sectors in developing alternative solutions to ease the shortage, it will take several years before this will come to full implementation. Conservation of energy through power management is the simplest and closest to implement at this time. Filipino households need to be motivated to use smart energy conservation. The introduction of Gamification as a method of motivations has found its use in many applications. In this study the possibility of Gamification to encourage the use of smart energy conservation is tested. In this study three game elements were used to develop the model for the game; these elements include incentives, competition and feedback. These three elements were implemented in an android game through a three step process; namely the Game Design where the theoretical framework of the game was created’ Game Implementation where the researchers create the functions for the game using the Java language and Eclipse IDE, and the Game Deployment where the researchers perform a bug test and advertise the project using Social Media and Live Advertising. The use of QR Codes was implemented for the participants to control switching on and off of appliances in the selected rooms.